Сметана. Технологія та якість - Шульга, Наталія Михайлівна; Млечко, Л. А. (My University, 2012)
Проведено аналіз основних причин формування вад у сметані. Наведені рекомендації щодо їх усунення. The analysis of the main courses of the defects formation of sour cream was conducted. The recommendations of their elimination were listed.
Keywords: якість сметани; sour cream quality; сепарування молока; пастеризація вершків; сквашування сметани; pasteurization of cream; sour cream fermentation; сепарування молока